Sejarah berbasis teenlit: Sebagai upaya peningkatan minat literasi sejarah peserta didik - Sukmono, Hilmy Aqila (Maliki Interdisciplinary Journal, 2024)
Teenlit, a popular literary genre, reflects the social life of teenagers with straightforward issues presented in a simple way. The study of popular literature, including teen literature, has become a serious focus in the academic world. Teenlit raises straightforward issues and is presented in a simple way. This research aims to explore teenlit as a popular literary genre and its relevance in educational contexts. Popular literature, including teen lit, plays an important role in building adolescent literacy and can be used as an effective learning medium in schools. Teenlit offers stories that are authentic and close to teenagers’ everyday experiences, allowing them to be actively involved in the creative process. By utilizing teenlit in teaching literature, teachers can encourage discussions that build students’ understanding of the structure of literary works, moral values, and the development of language skills. In conclusion, teenlit is not just entertainment, but is also an effective educational tool in appreciating literature and forming adolescent literacy. This research has important implications for literature education in schools and can form the basis for further research in this area.